Modern Business Models and Features of E-Commerce in The Republic of Uzbekistan - Nasirova Zulfiya Xudayberganovna (European Science Publishing, 2023)
Developing modern e-commerce in the Republic of Uzbekistan and strengthening its place in the economy is intended to take advantage of the experience of developed countries in the field of e-commerce in the technical and technological capabilities of modern e-commerce and the further upgrade of business models.
Keywords: eCommerce, model, business, consumer, product, organization, website, government, service, market, telecommunications, sales.